Demographic Profile, Employment Status, Competencies, Skills and Values Acquired among Bachelor of Elementary Education Graduates - Sherralyn Lacay; Cenby Eppie Gaytos; Eddie Manzano (East Asian Journal of Multidisciplinary Research, 2023)
The College of Education at Eastern Samar State University—Guiuan Campus seeks to cultivate individuals who are globally competitive and value-driven. The researchers initiated a tracer study to evaluate the employability of elementary school graduates from the classes of 2016 to 2019. It also includes the values and abilities acquired and developed during their university tenure. A quantitative design and a descriptive survey were employed to examine the demographic profile, employment status, values, and skills that ESSU Guiuan graduates developed and acquired during their time there. The result of the study addresses the weaknesses and strengths of the curriculum, as well as its adequacy and the quality of the education offered in relation to the competencies required by local and global markets. Also, this study shows that not all BEED program graduates are LET passers but pursued to get  graduate degrees. In addition, the majority of graduates are employed as temporary or contract workers, and the majority of employed respondents work in their respective communities. In addition, skills in human relations and creativity received a high mean score, which the respondents interpreted as indicating a high level of acquisition, whereas other skills and competence were moderately acquired.